Endoscope-assisted low-temperature plasma radiofrequency ablation of intermuscular angiolipoma in the chest: a case report - Li, Yaoyao; Zhao, Ming; Wang, Xin; Rong, Jian; Wang, Jianing; Song, Mei (Frontiers in Pediatrics, 2025)
BackgroundEndoscope-assisted surgery (EAS) remains largely unexplored for intermuscular angiolipomas (IA) in children. This study reports a 6-year-old girl with a right chest angiolipoma who underwent EAS via a minintermuscular angiolipomaly invasive anterior axillary fold approach.MethodsFollowing ultrasonographic and magnetic resonance imaging revealing a provisional diagnosis of IA, the patient underwent endoscope-assisted low-temperature plasma radiofrequency ablation (LTPRA) under general anesthesia. The procedure was performed through a single 2 cm incision at the right anterior axillary fold utilizing a 5 mm 30° endoscope and pediatric-specific fine instruments.ResultsComplete resection of the angiolipoma was achieved with an operative time of 120 min and blood loss of 15 ml. Pathological examination confirmed angiolipoma. At 6-month follow-up, no recurrence and satisfactory wound healing have been observed.ConclusionEAS proves a feasible and effective therapeutic option for complex anatomical-site angiolipomas due to its efficacy in complete excision and superior cosmetic outcomes. By integrating endoscopic visualization with precise plasma ablation, this technique significantly reduces neurovascular injury risks during deep intermuscular tumor dissection, offering a novel minintermuscular angiolipomaly invasive strategy for lesions in regions challenging for conventional open surgery.